Curating practical theological space: what is it, and who is it for?. Issue 6 (2nd November 2022) - Cross, Katie; Jordan, Elizabeth
ABSTRACT: This short article takes the form of a conversation between two members of the editorial board of the journal of Practical Theology. They consider both the journal and its scope, and the discipline more widely.